Analysis of factors affecting purchase decision of protein powder products I-CON Nutrition in jabodetabek - Elisabeth, Laura (Enrichment : Journal of Management, 2024)
This study aims to identify and analyze the factors that influence consumer purchase decisions for I-CON NUTRITION Protein Powder in the Jabodetabek area. The factors analyzed include product quality, price, promotion, lifestyle, electronic word of mouth (E-WOM), and service quality. Data were collected through an online questionnaire distributed to 228 respondents and analyzed using SmartPLS 4.0.9.9. The results show that product quality, price, promotion, and service quality have a positive and significant impact on purchase decisions, while lifestyle and E-WOM also play a significant role, albeit with a smaller effect. This study provides managerial implications for I-CON NUTRITION to enhance product quality, strengthen promotional strategies, and improve customer service quality to increase consumer purchase decisions. The findings also suggest that the company should focus more on consumers' healthy lifestyles and leverage the influence of E-WOM in their marketing strategies